2014
DOI: 10.1162/rest_a_00365
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Discrimination or Prejudice? A Large Sample Field Experiment

Abstract: A model of racial discrimination provides testable implications for two features of statistical discriminators: differential treatment of signals by race and heterogeneous experience that shapes perception. We construct an experiment in the U.S. rental apartment market that distinguishes statistical discrimination from taste-based discrimination. Responses from over 14,000 rental inquiries with varying applicant quality show that landlords treat identical information from applicants with African-American and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(142 citation statements)
references
References 27 publications
2
132
1
Order By: Relevance
“…Thus "positive response" is a subgroup of "simple response", but, as some studies have reported only one type of responses and as these different types of responses do not represent the same thing, it is maybe rather wise not to mix corresponding odd-ratio. Indeed, despite its practicality, comparing simple response rates may not be the best way to determine discrimination and might tend to underestimate it, "to the extent that majority rates could include more positive responses than minority rates" (Ewens et al, 2014). Fortunately, our database has more positive responses ratios than simple ones because it seems to become the norm in this literature despite the fact that it is easier for authors to record simple response rates for each ethnic group than positive response rates that require large sorting.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus "positive response" is a subgroup of "simple response", but, as some studies have reported only one type of responses and as these different types of responses do not represent the same thing, it is maybe rather wise not to mix corresponding odd-ratio. Indeed, despite its practicality, comparing simple response rates may not be the best way to determine discrimination and might tend to underestimate it, "to the extent that majority rates could include more positive responses than minority rates" (Ewens et al, 2014). Fortunately, our database has more positive responses ratios than simple ones because it seems to become the norm in this literature despite the fact that it is easier for authors to record simple response rates for each ethnic group than positive response rates that require large sorting.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…We included data from 25 studies, covering 14 countries: France (Acolin et al, 2016, Bunel et al, 2017, Bunel et al 2016, Le Gallo et al, 2017, Canada (Hogan, Berry, 2011), Czech Republic (Bartoš et al, 2016), Slovakia (Sacherová, 2016), Finland (Öblom and Antfolk, 2017), Denmark (Herby and Nielsen, 2015), Germany (Auspurg et al, 2017, Team BR Data andSpiegel Online, 2017), Italy (Baldini and Federici, 2011), Norway (Andersson et al, 2012), Spain (Bosch et al, 2010, Bosch et al, 2015, Sweden (Ahmed et al, 2010, Ahmed and Hammarstedt, 2008, Carlsson and Eriksson, 2013, Iceland (Björnsson et al, 2017), Israel (Sansani, 2017) and finally USA (Carpusor and Loges, 2006, Ewens et al, 2014, Friedman et al, 2010, Hanson and Hawley, 2011, Hanson and Santas, 2014, which are countries very similar in terms of development, whether human or economic.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Field experiments show that individuals who are identical except for a group characteristic (gender, race, etc.) are treated differently in the housing market (Andersson et al, 2012;Carlsson and Eriksson, 2014;Ewens et al, 2014) and in the labor market (Bertrand and Mullainathan, 2004;Carlsson and Rooth, 2007). A critique of field studies made by Heckman (1998) is that 1 Balsa et al (2005) use a cross-section of black and white patients, and find that the probability of being diagnosed with depression and mental health problems is reduced for black patients relative to white patients.…”
Section: Detecting Discrimination In Health Carementioning
confidence: 99%
“…4 This can be true if CMs regard informal care as a free resource, because, as long as informal care is provided, the benefit of doing so outweighs the cost, or if the CMs are only concerned about the health of patients.5 This closely follows the four-stage process of matching tenants to apartments inEwens et al (2014).6 As will be made clear later, we are considering four groups defined by the gender of the patient and gender of the patient's child, i.e., g i ∈ {FatherSon, FatherDaughter, MotherSon, MotherDaughter}.7 Phelps (1972) assumes the same utility function for employers hiring workers with unobservable quality. Please cite this article in press as: Jakobsson, N., et al, Gender bias in public long-term care?…”
mentioning
confidence: 99%